Aflatoxin contamination of milk produced in peri-urban farms of Pakistan: Prevalence and contributory factors - Yunus, A.W.; Ullah, Aman; Lindahl, Johanna F.; Anwar, Z.; Ullah, Atta; Saif, S.; Ali, M.; Zahur, A.B.; Irshad, H.; Javaid, S.; Imtiaz, N.; Farooq, U.; et al. (Frontiers Media, 2020)
Aflatoxin M1 contamination of milk in Pakistan, like many developing countries, is poorly understood. The present study was therefore conducted to determine AFM1 contamination of milk and its contributory factors in Pakistan. We sampled milk and feedstuffs from 450 peri-urban dairy farms in seven major cities following a cross-sectional study design. Analysis of milk using ELISA revealed high contamination with an overall average of 3164.5 ng of AFM1/L, and significant differences (p < 0.001) between cities. The milk sampled from Gilgit, in northern hilly areas, had an average AFM1 level of 92.5 ng/L. Milk from other cities had 3529.7 ng/L average contamination, with only 5.7% samples qualifying the maximum tolerable limit of 500 ng of AFM1/L. Heavy mean aflatoxin contamination was found in bakery waste (724.6 μg/kg), and cottonseed cake (600.8 μg/kg). Rest of the other feedstuffs had moderate to low mean aflatoxin contamination, ranging from 66.0 μg/kg in maize stover to 3.4 μg/kg in wheat bran. The mean aflatoxin level in commercial dairy concentrates was 32.7 µg/kg. About 80% of the total aflatoxin intake of dairy animals was contributed by cottonseed cake alone due to its high aflatoxin contamination and proportion in dairy rations. On-farm storage time of oilseed cakes varied (p < 0.01) in different cities but was not associated with aflatoxin contamination. The exceptionally high AFM1 contamination suggests that milk from peri-urban dairy farms is a serious public health threat in Pakistan. This situation can be mitigated by reducing aflatoxin contamination in cottonseed cake and promoting the use of commercial concentrates and other feedstuffs with low contamination.